Relationship Knowledge Attitudes Toward Sexual Abuse Prevention In Children 3-6 Years - Neni Maemunah (University of Muhammadiyah Malang, 2016)
There are many sexual violence cases specially for children, to cope a mother’s knowledge is really needed to attain sexual abuse prevention in children, the mother should have knowledge either what child sexual abuse is, general characteristic, attitude, detect the child’s insulting victim, or bad impact, cause and prevention in order to the mother can support child sexual abuse prevention. This research is aimed to know the relationship knowledge attitudes toward sexual abuse prevention in children 3-6 years. The research method of the study is correlational through cross sectional approach. The number of population is 82 people and the sample is 45 people and the sampling technique is proportionate stratified random. The data analysis is spearman’s rho test. The research result is gotten descriptive analysis presents that mother’s knowledge is much enough is that 20 people (44%). Most of mothers’ attitude categorizes in favorable attitude as many as 31 people (69%). It is concluded that there is significance relationship between mother’s knowledge and the sexual abuse prevention attitude in children 3-6 years in the village of north Mondoroko Bajararum Rw 05 Singosari. This study is expected that the mother could increase the knowledge related to sexual abuse in order to have the attitude to support sexual abuse prevention, such as giving the sex education in early age, teaching to wear the cloths well, teaching the child to distinguish the personal touch, teaching the child to have open minded character, etc.